Overcoming Barriers to Improve Halal Compliance in Indonesia: Mengatasi Hambatan untuk Meningkatkan Kepatuhan Halal di Indonesia - Rahma, Anita Rizkia; Phahlevy, Rifqi Ridlo (Universitas Muhammadiyah Sidoarjo, 2024)
General Background: The regulation of halal products in Indonesia is critical for ensuring compliance with Islamic dietary laws and consumer protection. Specific Background: The Halal Product Guarantee Agency (BPJPH), established in 2014, manages halal certification, but its effectiveness is hindered by limited public resources, complex certification processes, and low public awareness. Knowledge Gap: While existing literature addresses the legal aspects of halal regulation, there is insufficient exploration of the socio-legal dynamics influencing compliance and enforcement in Indonesia. Aims: This study aims to analyze BPJPH's regulatory effectiveness in the halal certification process, identify the challenges faced, and propose actionable solutions. Results: Utilizing socio-legal methods, including legal analysis and interviews with key stakeholders such as the Ministry of Religion and the Indonesian Ulema Council, the findings reveal that BPJPH's implementation efforts are hindered by resource constraints and public ignorance about halal certification's significance. Novelty: This research uniquely integrates legal and social perspectives to provide a comprehensive understanding of the regulatory landscape, highlighting the interplay between law and societal values in shaping halal compliance. Implications: The study emphasizes the need for improved socialization, inter-agency collaboration, and educational initiatives to raise public awareness and enhance enforcement of halal products in Indonesia. Highlights: Regulatory Framework: BPJPH enforces halal certification under Law Number 33 of 2014. Challenges: Resource limitations and public ignorance hinder effective implementation. Socio-Legal Approach: Combines legal and social perspectives on halal compliance. Keywords: halal certification, BPJPH, socio-legal methods, regulatory effectiveness, public awareness